Shoulder palsy following SARS‐CoV‐2 infection: two cases of typical Parsonage–Turner syndrome. (15th July 2022) - Fortanier, Etienne; Le Corroller, Thomas; Hocquart, Marie; Delmont, Emilien; Attarian, Shahram
Abstract: Background and purpose: Coronavirus disease 2019 (COVID‐19) is now known to cause neurological complications in both the central and the peripheral nervous system. Two new cases of typical neuralgic amyotrophy or Parsonage–Turner (PT) syndrome following coronavirus 2 infection (SARS‐CoV‐2) are reported here with explicit electrophysiological and imaging pathological features, underlining the possible association between COVID‐19 and PT syndrome. Case reports: Case 1 was a 45‐year‐old schoolteacher presenting with acute pain in the right shoulder a few days after SARS‐CoV‐2 infection, with shoulder abduction and elbow flexion weakness. Needle electromyography showed a decrease in motor unit recruitment in the biceps brachii, and plexus magnetic resonance imaging (MRI) revealed a hyperintense signal involving the right C6 root and the superior truncus of the brachial plexus. Case 2 was a 21‐year‐old man hospitalized for dyspnea secondary to SARS‐CoV‐2 infection. Ten days after symptom onset, he presented right shoulder pain with difficulty in raising his right arm, revealing an isolated deficit of the serratus major muscle with a right scapula winging. Electrophysiological evaluation exhibited an isolated involvement of the long thoracic nerve with a neurogenic recruitment pattern in the serratus major muscle. Plexus MRI displayed a thickening and hyperintense signal involving the right long thoracic nerve. Discussion: Parsonage–Turner syndrome triggered by SARS‐CoV‐2 seems to present clinical, electrophysiological and MRI characteristics similar to classic para‐infectious PT syndrome, including the time frame between viral infection and neurological symptom onset. Conclusion SARS‐CoV‐2 might be a new infectious trigger of PT syndrome. Abstract : Two acute painful shoulder weakness cases in coronavirus disease 2019 patients are presented, in favor of Parsonage–Turner (PT) syndrome secondary to coronavirus 2 infection (SARS‐CoV‐2). Analyzing our two cases, PT syndrome triggered by SARS‐CoV‐2 seems to present electrophysiological and magnetic resonance imaging characteristics similar to classical PT syndrome, including the time frame between viral infection and neurological symptom onset.